A Deadly Organometallic Luminescent Probe: Anticancer Activity of a ReI Bisquinoline Complex. Issue 9 (24th January 2014) - Kitanovic, Igor; Can, Suzan; Alborzinia, Hamed; Kitanovic, Ana; Pierroz, Vanessa; Leonidova, Anna; Pinto, Antonio; Spingler, Bernhard; Ferrari, Stefano; Molteni, Roberto; Steffen, Andreas; Metzler‐Nolte, Nils; et al.
Abstract The photophysical properties of [Re(CO)3(L‐N3)]Br (L‐N3=2‐azido‐N, N‐bis[(quinolin‐2‐yl)methyl]ethanamine), which could not be localized in cancer cells by fluorescence microscopy, have been revisited in order to evaluate its use as a luminescent probe in a biological environment. The ReI complex displays concentration‐dependent residual fluorescence besides the expected phosphorescence, and the nature of the emitting excited states have been evaluated by DFT and time‐dependent (TD) DFT methods. The results show that fluorescence occurs from a 1LC/MLCT state, whereas phosphorescence mainly stems from a 3LC state, in contrast to previous assignments. We found that our luminescent probe, [Re(CO)3(L‐N3)]Br, exhibits an interesting cytotoxic activity in the low micromolar range in various cancer cell lines. Several biochemical assays were performed to unveil the cytotoxic mechanism of the organometallic ReI bisquinoline complex. [Re(CO)3(L‐N3)]Br was found to be stable in human plasma indicating that [Re(CO)3(L‐N3)]Br itself and not a decomposition product is responsible for the observed cytotoxicity. Addition of [Re(CO)3(L‐N3)]Br to MCF‐7 breast cancer cells grown on a biosensor chip micro‐bioreactor immediately led to reduced cellular respiration and increased glycolysis, indicating a large shift in cellular metabolism and inhibition of mitochondrial activity. Further analysis of respiration of isolated mitochondria clearly showed that mitochondrial respiratory activity was a direct target of [Re(CO)3(L‐N3)]Br and involved two modes of action, namely increased respiration at lower concentrations, potentially through increased proton transport through the inner mitochondrial membrane, and efficient blocking of respiration at higher concentrations. Thus, we believe that the direct targeting of mitochondria in cells by [Re(CO)3(L‐N3)]Br is responsible for the anticancer activity.